Tinjauan Yuridis Perlindungan Hukum Bagi Pekerja Perempuan Ditinjau Dari Perspektif Hukum Ketenagakerjaan UU No.13 Tahun 2003 Tentang Ketenagakerjaan (International Forum of Researchers and Lecturers, 2023)
Women workers in Indonesia have an important role in the Indonesian economy. Women and men as subjects and objects of development have the same rights, obligations and opportunities. Employers may not discriminate against women workers in terms of wages, promotion and career development. Writing this is to determine the need for legal protection for women workers. Therefore, the state provides legal protection, namely Law Number 13 of 2003 concerning Manpower to provide protection for women workers.